The effects of occipital and parietal tDCS on chronic visual field defects after brain injury - Diana, Lorenzo; Casati, Carlotta; Melzi, Lisa; Bianchi Marzoli, Stefania; Bolognini, Nadia (Frontiers in Neurology, 2024)
Introduction Homonymous visual field defects (HVFDs) following acquired brain lesions affect independent living by hampering several activities of everyday life. Available treatments are intensive and week- or month-long. Transcranial Direct current stimulation (tDCS), a plasticity-modulating non-invasive brain stimulation technique, could be combined with behavioral trainings to boost their efficacy or reduce treatment duration. Some promising attempts have been made pairing occipital tDCS with visual restitution training, however less is knows about which area/network should be best stimulated in association with compensatory approaches, aimed at improving exploratory abilities, such as multisensory trainings. Methods In a proof-of-principle, sham-controlled, single-blind study, 15 participants with chronic HVFDs underwent four one-shot sessions of active or sham anodal tDCS applied over the ipsilesional occipital cortex, the ipsilesional or contralesional posterior parietal cortex. tDCS was delivered during a compensatory multisensory (audiovisual) training. Before and immediately after each tDCS session, participants carried out a visual detection task, and two visual search tasks (EF and Triangles search tests). Accuracy (ACC) and response times (RTs) were analyzed with generalized mixed models. We investigated differences in baseline performance, clinical-demographic and lesion factors between tDCS responders and non-responders, based on post-tDCS behavioral improvements. Lastly, we conducted exploratory analyses to compare left and right brain-damaged participants. Results RTs improved after active ipsilesional occipital and parietal tDCS in the visual search tasks, while no changes in ACC were detected. Responders to ipsilesional occipital tDCS (Triangle task) had shorter disease duration and smaller lesions of the parietal cortex and the superior longitudinal fasciculus. On the other end, on the EF test, those participants with larger damage of the temporo-parietal cortex or the fronto-occipital white matter tracts showed a larger benefit from contralesional parietal tDCS. Overall, the visual search RTs improvements were larger in participants with right-sided hemispheric lesions. Conclusion The present result shows the facilitatory effects of occipital and parietal tDCS combined with compensatory multisensory training on visual field exploration in HVFDs, suggesting a potential for the development of new neuromodulation treatments to improve visual scanning behavior in brain-injured patients.